When the Injury Heals but the Athlete Does Not: Psychological Barriers to return to Sport – A Narrative Review - Arczyńska-Antkiewicz, Aleksandra; Antkiewicz, Mikołaj; Czechowicz, Paweł; Czechowicz, Justyna; Zając, Gabriela; Drozd, Maria; Łobaza, Paulina; Kudła, Martyna; Krawczyk, Agata; Pawełczak, Natalia; Kołkowicz, Dorota; Kociuba, Julia; et al. (Journal of Education, Health and Sport, 2026)
Introduction and purpose: Sports injury is often treated as a physical event, although its consequences may extend to mood, anxiety, rehabilitation adherence, confidence, and return-to-play outcomes. This review summarizes evidence on depressive and anxiety symptoms after sports injury, with emphasis on their course, risk factors, and clinical implications. Material and method: A narrative review was conducted using PubMed as the primary database, with supplementary searching in Scopus. Publications from January 2000 to April 2026 were considered, prioritizing systematic reviews, meta-analyses, cohort and prospective studies, consensus statements, and clinically relevant observational research. Results: Depressive and anxiety symptoms may appear shortly after injury, persist during prolonged rehabilitation, and become especially relevant during return to play. Key risk factors include injury severity, prolonged time-loss, strong athletic identity, insufficient social support, previous mental health vulnerability, and pressure within competitive sport environments. Fear of reinjury and low psychological readiness may remain despite satisfactory physical recovery. Conclusions: Depression and anxiety are clinically meaningful components of post-injury recovery. Screening, education, interdisciplinary care, timely referral, and assessment of psychological readiness should be integrated into rehabilitation and return-to-play decisions to support safer and more sustainable return.